Motivational Interviewing Intervention on Health‐Seeking Behaviors of Pregnant Women in Western Kenya. Issue 2 (June 2014) - Gisore, Peter; Kaseje, Dan; Were, Fred; Ayuku, David
<x xml:space="preserve">Abstract</x> We studied the effect of using Motivational Interviewing Intervention (MII) on health facility delivery and newborn care practices among pregnant women receiving Care of the Mother and Newborn at Home (CNH) visits by Community Health Workers (CHWs). Near‐Term women who had received at least one CHW home visit, were randomly assigned to one session of MII (intervention) or no MII (Control). Fifty five (55%) of intervention women, compared to 35% of control women delivered in health facilities. Intervention women also understood the need to breastfeed exclusively for 6 months better than controls (P = 0.000), and had a p‐value of 0.07 for breastfeeding within one hour after birth. We concluded in the context of CHW Home visit program, adding may improve perinatal care.